Study of some Population Parameters in Captive Bred Tigers - Saharia, V. B. (Indian Forester, 1979)
Breeding of white tiger has been done over a period of last 20 years in the Delhi Zoological Park. These captive bred tigers in the Delhi Zoological Park have also been distributed to other different zoos in India as well as in other parts of the world. A complete genealogical chart of these captive bred tigers in different locations has been maintained by the Delhi Zoo. This data on the breeding of tiger over the past 20 years has been utilised in studying various detailed parameters to gain an insight into the reproductive potential and breeding behaviour of the tiger. Some of the results can be projected even on free living animals in so far as they highlight biological potential of the species.